Resilience in trade fairs: A study in Brazilian context - Gerhard, Felipe; Peñaloza, Verónica (Interações, 2018)
This research aims to analyze through the lenses of resilience, the collective construction and social representation of a trade fair by its actors. To this, an exploratory qualitative case study was conducted with vendors of a large trade fair in the city of Fortaleza. The main reasons that provide growth, reduction or stability of these environments are not restricted to purely financial factors; the resilience of trade fairs transcends a marketing perspective, achieving also social and cultural dimensions.